Serosurvey of Trypanosoma cruzi in persons experiencing homelessness and shelter workers of Brazil - Kmetiuk, Louise Bach; Gonçalves, Gustavo; Chechia Do Couto, Anahi; Biondo, Alexander Welker; Figueiredo, Fabiano Borges (Frontiers in Public Health, 2023)
Although Chagas disease, caused by Trypanosoma cruzi, has been associated with social vulnerability worldwide, producing disability and mortality, no study to date has assessed this protozoal infection in persons experiencing homelessness. Accordingly, the present study aimed to assess anti-T. cruzi antibodies by Wiener Chagatest ELISA recombinant v.3.0 in serum samples of persons experiencing homelessness and related shelter workers in São Paulo, a city with reported vectors but no recent autochthonous case report. Overall, seropositivity to T. cruzi resulted in three of 203 (1.5%) persons experiencing homelessness and two of 87 (2.3%) shelter workers, with similar seroprevalence likely associated with their past social vulnerability. Although the seropositivity in persons experiencing homelessness and shelter workers was within 0 to 25.1% seroprevalence for chronic Chagas disease in the general Brazilian population, the disease has almost decreased 2-fold from the 1980s to 2000s, and such a wide range may not reflect the local disease status. In addition, the authors hypothesized that the similar seroprevalence and exposure between homeless persons and shelter workers herein may be more associated with shared past and present low-income social vulnerability than migratory movements, which may also include infection by sharing injecting drugs, vertical transmission, or blood transfusion. Thus, future studies are needed to confirm the active transmission of Chagas disease in São Paulo city. Moreover, Chagas disease should be considered as differential diagnosis in homeless persons and shelter workers, even in major disease-free Brazilian or other worldwide cities, mostly due to early exposure and vulnerable living conditions.